Fast sorting of CD4+ T cells from whole blood using glass microbubbles - Hsu, Chia-Hsien (Technology (Singap World Sci), 2015)
The isolation of CD4 positive T lymphocyte (CD4+) from peripheral blood is important for monitoring patients after HIV infection. Here, we demonstrate a fast isolation strategy for CD4+ cells that involves mixing blood and glass microbubbles. After the specific binding of target cells to the microbubbles carrying specific antibodies on their surface, target cells will spontaneously float to the top of the blood vial and can be quickly separated. Using this strategy, we demonstrate that the isolation of CD4+ cells in less than 5 minutes and with better than 90% efficiency. This strategy for cell isolation based on buoyancy and glass microbubbles is quick and inexpensive, minimizes blood handling, does not require magnetic fields, or centrifugation equipment, and could lead to new, efficient strategies for AIDS diagnosis in resource-limited areas.